Paleozoic Laurentia-Gondwana Interaction and the Origin of the Appalachian-Andean Mountain System - Dalziel, Ian W.D. (1994)
Fil: Dalziel, Ian W.D.. Institute for Geophysics. University of Texas. Austin. Texas; USA